2018
DOI: 10.1158/1538-7445.sabcs17-p3-14-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-14-01: Effects of adding budesonide or colestipol to loperamide prophylaxis on neratinib-associated diarrhea in patients with HER2+ early-stage breast cancer: The CONTROL trial

Abstract: Background: Neratinib is an irreversible pan-HER tyrosine kinase inhibitor. Results from the randomized, placebo-controlled, Phase III ExteNET study demonstrated that neratinib significantly improves 24-month iDFS in patients (pts) with trastuzumab-treated early-stage HER2+ breast cancer (HR 0.67; 95% CI 0.50–0.91; p=0.009) [Chan et al. Lancet Oncol 2016]. In ExteNET, loperamide prophylaxis was not mandated, and diarrhea was the most commonly observed toxicity (grade 3, 39.8%). To reduce neratinib-associated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The results of the trial also showed that treatment with neratinib plus capecitabine statistically significantly improved time to intervention for symptomatic brain metastases, a secondary endpoint of the study, versus lapatinib plus capecitabine. Prophylactic treatment for diarrhea has improved the major clinical side effect of neratinib [141], allowing further investigation of neratinib in additional clinical settings for patients with HER2-positive or HER2- mutated tumors. Given its unique potent, irreversible, pan-HER kinase inhibitor properties, neratinib has potential to synergize with a variety of molecular targeted therapies, such as trastuzumab, T-DM1, anti-estrogens, Src inhibitors, CDK4/6 inhibitors, HSP90 inhibitors, and HDAC inhibitors, in the treatment-naive or treatment-refractory settings.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the trial also showed that treatment with neratinib plus capecitabine statistically significantly improved time to intervention for symptomatic brain metastases, a secondary endpoint of the study, versus lapatinib plus capecitabine. Prophylactic treatment for diarrhea has improved the major clinical side effect of neratinib [141], allowing further investigation of neratinib in additional clinical settings for patients with HER2-positive or HER2- mutated tumors. Given its unique potent, irreversible, pan-HER kinase inhibitor properties, neratinib has potential to synergize with a variety of molecular targeted therapies, such as trastuzumab, T-DM1, anti-estrogens, Src inhibitors, CDK4/6 inhibitors, HSP90 inhibitors, and HDAC inhibitors, in the treatment-naive or treatment-refractory settings.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of grade III diarrhea reported in the approval study was 39.8%, which led to termination of the therapy by 16.8% of patients. The CONTROL study compared an intensified loperamide regimen (12 mg/day, d1–14, followed by 6 – 8 mg/day, d15–56) with combinations of loperamide and the steroid budesonide or the cholesterol-lowering drug colestipol 28 . Grade III diarrhea occurred in 30.7, 25.0 and 7.7% of patients, and therapy termination rates were 20.4, 9.4 and 0%, respectively.…”
Section: Supportive Therapymentioning
confidence: 99%
“…In der Zulassungsstudie zeigte sich eine Diarrhörate Grad 3 von 39,8%, die zu einem Abbruch bei 16,8% der Patientinnen führte. In der CONTROL-Studie wurde ein intensiviertes Loperamid-Schema (12 mg/d, d1–14, gefolgt von 6 – 8 mg/d, d15–56) mit den Kombinationen von Loperamid und dem Steroid Budenosid oder dem Cholesterinsenker Colestipol verglichen 28 . Es zeigten sich Grad-3-Diarrhöen in 30,7, 25,0 und 7,7% mit Abbruchraten von 20,4, 9,4 und 0%.…”
Section: Diarrhökontrolle In Der Hand Des Behandelnden Arztesunclassified
“…Patients reported a transient reduction in health-related quality of life during the first month of therapy, followed by steady recovery toward baseline. The follow-up CONTROL trial (Hurvitz et al, 2017) showed the incidence of diarrhea to be further reduced as compared to the ExteNET trial with the use of prophylactic loperamide alone or in combination with budesonide, or colestipol.…”
Section: Adjuvant Systemic Therapymentioning
confidence: 99%